2002
DOI: 10.1016/s0960-9822(02)01069-2
|View full text |Cite
|
Sign up to set email alerts
|

Rho-Kinase and Myosin-II Control Phagocytic Cup Formation during CR, but Not FcγR, Phagocytosis

Abstract: Phagocytosis through Fcgamma receptor (FcgammaR) or complement receptor 3 (CR) requires Arp2/3 complex-mediated actin polymerization, although each receptor uses a distinct signaling pathway. Rac and Cdc42 are required for actin and Arp2/3 complex recruitment during FcgammaR phagocytosis, while Rho controls actin assembly at CR phagosomes. To better understand the role of Rho in CR phagocytosis, we tested the idea that a known target of Rho, Rho-kinase (ROK), might control phagocytic cup formation and/or engul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
208
4
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(224 citation statements)
references
References 29 publications
9
208
4
3
Order By: Relevance
“…The fact that Rac1 activity is not required for this uptake mechanism provides further support for our conclusion. 33 To confirm further the involvement of distinct signaling pathways involving phagocytosis and fusion, we observed that MCP-1-null macrophages, which are inherently deficient in fusion, displayed normal engulfment of microspheres.…”
Section: Inhibition Of Fbgc Formation In Vivo By Prolonged Release Ofmentioning
confidence: 85%
“…The fact that Rac1 activity is not required for this uptake mechanism provides further support for our conclusion. 33 To confirm further the involvement of distinct signaling pathways involving phagocytosis and fusion, we observed that MCP-1-null macrophages, which are inherently deficient in fusion, displayed normal engulfment of microspheres.…”
Section: Inhibition Of Fbgc Formation In Vivo By Prolonged Release Ofmentioning
confidence: 85%
“…Phagocytosis involves the active protrusion of lamellipodia around an object that is to be engulfed, and several myosin classes are involved in this process. Myosin Ic 9 and myosin X 10 seem to be key players in the extension of phagocytic cup pseudopods, whereas myosin II promotes closure of the cup 11 (FIG. 2).…”
Section: Processivitymentioning
confidence: 99%
“…The negative effect of Rho/ROCK during engulfment of apoptotic cells differs from other types of phagocytosis mediated via the complement receptor and Fc receptor, respectively. Rho and ROCK have been shown to be critical for complement receptor-mediated phagocytosis, and but not for Fc receptor-mediated phagocytosis [12,100]. Recently, ROCk2 activity, but not ROCK1 activity, has been shown to facilitate phagocytic uptake of fibronectin-coated beads [151].…”
Section: Phagocytosis Of Apoptotic Cellsmentioning
confidence: 99%